Udział wspólnot zakonnych w kształtowaniu języka religijnego = The participation of conventual communities in shaping the religious language - Bieńkowska, Danuta; Umińska-Tytoń, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the study is to identify to what extent the conventual congregations forming close, closed communicative communities, affected the quality of the means of religious communication, which is the religious variety of Polish language. Of the main interest are the names of non-general incidence, specific to a particular community, concerning: symbols of the same designates using different names, using the same names in different communities to denote different concepts and designates, terms used only in one community to expose its specific concepts, actions and habits.
Keywords: wspólnota zakonna; język religijny; conventual communities; religious language